Erratum to the article: “Bifunctional gallium cation chelators” - A. G. Polivanova; I. N. Solovieva; D. O. Botev; D. Y. Yuriev; A. N. Mylnikova; M. S. Oshchepkov (Тонкие химические технологии, 2022)
Page 126, in Acknowledgments instead of